'The Question of Pratt': A Syndicalist Conundrum. Issue 1 (April 2020) - Eyben, Rosalind
Abstract : This article takes a reflexive approach in a case study of the dubious career of a syndicalist trade unionist and journalist just before and during the First World War. E.L. Pratt was an elusive trickster and a convincing (self-) publicist, who between 1914 and 1918 established three trade unions and successively edited two major syndicalist journals. A wide range of fragmentary primary sources are used to explore how Pratt's syndicalism derived from a background as a waiter in the British catering sector that experienced its first nationwide strikes in 1913. Referencing the transnational turn to labour history, the article interrogates Pratt's international connections and looks at why and how he moved into the syndicalist mainstream, associating with Tom Mann and the engineering workers in the rank-and-file movement. I explore the eventual crisis in his comradely relations that led to what syndicalist leader Jack Tanner referred to in 1919 as 'the question of Pratt'. Our subject has merited only a couple of footnotes in syndicalist historiography, begging the question whether his comrades may have chosen not to remember him.